A protease additive increases fermentation of alfalfa diets by mixed ruminal microorganisms in vitro - Colombatto, Dario (2009)
In vitro experiments were conducted to examine the characteristics and mode of action of a protease that increased the ruminai fiber digestibility of alfalfa hay. A commercial source of protease (Protex 6L, Genencor Int., Rochester, NY), already characterized for its main activities, was further analyzed to determine protease activity in response to pH, molecular size by SDS-PAGE, specificity to degrade model or feed substrates, response to autoclaving, and action of specific protease inhibitors in the absence or presence of ruminai fluid. In addition, batch culture in vitro incubations in buffered ruminal fluid were conducted to compare the enzyme product with purified protease sources, and dose-response studies (0 to 10 μL/g of forage DM) were carried out using alfalfa hay as a substrate. The enzyme product was shown to be an alkaline protease (optimum pH >8.5) of approximately 30 kDa. Specificity in the absence of ruminai fluid showed that the enzyme was active against gelatin and casein to the same extent, whereas it had limited (21% of the total) activity on BSA. In the presence of ruminai fluid and with the use of feed substrates, the protease increased (P < 0.05) 22-h IVDMD (%) of alfalfa hay, fresh corn silage, dry-rolled corn, and a total mixed ration composed of the 3 ingredients (39.5 vs. 44.7; 50.3 vs. 54.5; 63.8 vs. 68.4; and 55.4 vs. 56.4 for control vs. protease for each feed, respectively). Inhibitor studies in the absence of ruminai fluid indicated that the enzyme was inhibited most by a serine protease inhibitor but not by cysteineor metalloprotease inhibitors (10 vs. 1.9 and 0.1%, respectively). In the presence of ruminal fluid, the serine protease inhibitor reversed (P < 0.05) the increase in alfalfa IVDMD achieved by the enzyme product, such that IVDMD was similar to that of the control treatment. Comparisons among different proteases revealed that only pure subtilisin achieved increases in IVDMD that were similar to those with protease, suggesting the serine protease was subtilisin-like (EC 3.4.1.62). Dose-response studies using alfalfa hay as substraje showed quadratic responses in IVDMD, NDF digestion, and hemicellulose and protein disappearance. It is postulated that this enzyme acts by removing structural proteins in the cell wall, allowing ruminal microbes to gain faster access to digestible substrates.